Pengaruh Rasio Profitabilitas, Likuiditas, dan Aktivitas Terhadap Harga Saham Perusahaan Sektor Kesehatan yang Terdaftar di Bursa Efek Indonesia Periode 2021–2025 - Haris Saputra; Elmira Siska (Ekopedia: Jurnal Ilmiah Ekonomi, 2026)
This study aims to empirically examine the influence of profitability, liquidity, and activity ratios on the stock prices of healthcare sector companies listed on the Indonesia Stock Exchange (IDX) during the 2021–2025 period. This study employs a quantitative method with a causal-associative approach, analyzing the relationship between Return on Assets (ROA) as a profitability indicator, Current Ratio (CR) as a liquidity indicator, and Total Asset Turnover (TATO) as an activity indicator, which serve as independent variables, against stock price as the dependent variable. The results indicate that profitability ratio (ROA), liquidity ratio (CR), and activity ratio (TATO) each partially have no significant effect on stock price. Furthermore, all three variables simultaneously also show no significant effect on the stock price of healthcare sector companies listed on the IDX during the observed period. These findings suggest that stock price movements in the healthcare sector during the 2021-2025 transitional period may be driven by factors beyond fundamental financial ratios, warranting further investigation into non-financial and macroeconomic determinants.